2009
DOI: 10.2169/internalmedicine.48.1869
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Nonalcoholic Steatohepatitis: Advantages and Pitfalls of Ultrasonography and Computed Tomography

Abstract: Objective The present study was performed to clarify the ability of ultrasonography (US) and computed tomography (CT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 29 publications
1
47
0
17
Order By: Relevance
“…It is, however, well known that serum transaminases may be normal in patients with histologically proven NAFLD and are not useful for making this diagnosis. 42,43 We also clearly showed that a low metformin dose (1 g per day) is sufficient to induce clinically significant beneficial effects on metabolic parameters. These effects are greater than those observed with diet alone, in spite of similar weight loss in the two groups.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is, however, well known that serum transaminases may be normal in patients with histologically proven NAFLD and are not useful for making this diagnosis. 42,43 We also clearly showed that a low metformin dose (1 g per day) is sufficient to induce clinically significant beneficial effects on metabolic parameters. These effects are greater than those observed with diet alone, in spite of similar weight loss in the two groups.…”
Section: Discussionmentioning
confidence: 75%
“…46 Moreover, the accuracy of US in detecting steatosis is not affected by obesity. 43 One limitation of US is to be somewhat operator-dependent when used for evaluating small changes in liver fat with time. 50 To circumvent this limitation, all US examinations were carried out by a single Another potential US limitation is its relative insensitivity in detecting hepatic steatosis when liver fibrosis is present.…”
Section: Discussionmentioning
confidence: 99%
“…86 Table 3 presents results of the imaging techniques used in diagnosis of NAFLD-NASH. 86,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] The underlying physical principle of imaging techniques are the same between adults and children. Consequently research in both age groups could be used to approve the use of these methods in pediatric field.…”
Section: Image Studiesmentioning
confidence: 99%
“…[93][94][95] Consequently, CT is not clinically acceptable for diagnosis of mild to moderate hepatic steatosis. 87,96 CT is associated with radiation exposure which limits its use for longitudinal studies and in children.…”
Section: Computed Tomography (Ct Scan)mentioning
confidence: 99%
“…Количественно оценить сте-пень выраженнос ти жировой инфильтрации в печени позволяет магнитно-резонансная томография с кон-трастированием. Очаги снижения интенсивности могут свидетельствовать о локальном накоплении жира в пе-чени [45,52].…”
unclassified